Experimental fracture resistance study for cracked bovine femur bone samples - M.R.M. Aliha; Hussein Ghazi; Farkhondeh Ataei (Fracture and Structural Integrity)
Crack growth and brittle fracture is one of the major failure modes in bone materials and therefore understanding the fracture behavior and affecting parameters on the crack growth resistance of bone is necessary for biomechanics researchers. In this paper, mode I fracture toughness value for the left and right femur bones of same bovine were measured experimentally using several single edge notch bend beam specimens (SENB) subjected to three-point bend loading in dry condition. The SENB specimens were cut along the longitudinal axis of bone but from different hoop directions. Fracture toughness results of sample prepared from the frontal part of bone were higher than the back or side sections. Depending on the location of sample, the fracture toughness of femur bone was varied from 5 to 10 MPa . Furthermore, the results obtained for similar location of both left and right femur bones were nearly identical. The fracture energy (Gf) of the tested specimens was also measured and it was found that a linear relation can be fitted to the (KIc)2 versus Gf results of the tested bovine bone.